Correction: Jung et al. Heat Integration of Liquid Hydrogen-Fueled Hybrid Electric Ship Propulsion System. J. Mar. Sci. Eng. 2023, 11, 2157 - Wongwan Jung; Jinkwang Lee; Daejun Chang (Journal of Marine Science and Engineering, 2024)
Error in Figure [...]